Deglacial history of the Pensacola Mountains, Antarctica from glacial geomorphology and cosmogenic nuclide surface exposure dating. (15th February 2017) - Bentley, M.J.; Hein, A.S.; Sugden, D.E.; Whitehouse, P.L.; Shanks, R.; Xu, S.; Freeman, S.P.H.T.
Abstract: The retreat history of the Antarctic Ice Sheet is important for understanding rapid deglaciation, as well as to constrain numerical ice sheet models and ice loading models required for glacial isostatic adjustment modelling. There is particular debate about the extent of grounded ice in the Weddell Sea embayment at the Last Glacial Maximum, and its subsequent deglacial history. Here we provide a new dataset of geomorphological observations and cosmogenic nuclide surface exposure ages of erratic samples that constrain the deglacial history of the Pensacola Mountains, adjacent to the present day Foundation Ice Stream and Academy Glacier in the southern Weddell Sea embayment. We show there is evidence of at least two glaciations, the first of which was relatively old and warm-based, and a more recent cold-based glaciation. During the most recent glaciation ice thickened by at least 450 m in the Williams Hills and at least 380 m on Mt Bragg. Progressive thinning from these sites was well underway by 10 ka BP and ice reached present levels by 2.5 ka BP, and is broadly similar to the relatively modest thinning histories in the southern Ellsworth Mountains. The thinning history is consistent with, but does not mandate, a Late Holocene retreat of the grounding line to a smaller-than-present configuration, as has been recently hypothesized based on ice sheet and glacial isostatic modelling. The data also show that clasts with complex exposure histories are pervasive and that clast recycling is highly site-dependent. These new data provide constraints on a reconstruction of the retreat history of the formerly-expanded Foundation Ice Stream, derived using a numerical flowband model. Highlights: New geomorphological observations and exposure ages for Pensacola Mountains, adjaecent to Foundation Ice Stream, Antarctica. Exposure ages show modest Holocene thinning between 10 and 2.5 ka BP, similar to nearby chronologies in Ellsworth Mountains. Data provide constraints for ice sheet modelling and are consistent with recent hypotheses of retreat in Late Holocene.